Surgical management and outcomes of spinal metastasis of malignant adrenal tumor: A retrospective study of six cases and literature review - Ni, Xiangzhi; Wang, Jing; Cao, Jiashi; Zhang, Kun; Hou, Shuming; Huang, Xing; Song, Yuanjin; Gao, Xin; Xiao, Jianru; Liu, Tielong (Frontiers in Oncology, 2023)
Purpose: Spinal metastasis of malignant adrenal tumor (SMMAT) is an extremely rare and poorly understood malignant tumor originating from the adrenal gland. The objective of this study is to elucidate the clinical characteristics and discuss surgical management and outcomes of SMMAT. Methods: Included in this study were six SMMAT patients who received surgical treatment in our center between March 2013 and February 2022. Their clinical data and outcomes were retrospectively analyzed to gain a better understanding of SMMAT. In addition, ten cases from the literature focusing on SMMAT were also reviewed. Results: Surgery was performed successfully, and the associated symptoms were relieved significantly in all patients postoperatively. The mean follow-up period was 26.1 (range 3-55) months. Two patients died of tumor recurrence 12 and 48 months after operation respectively. The other four patients were alive with no evidence of disease at the last follow-up. Conclusions: The prognosis of SMMAT is usually poor. Preoperative embolization and early surgical intervention with radical resection can offer satisfactory clinical outcomes. The patient's health status, preoperative neurological function, tumor location and the resection mode are potential prognostic factors of SMMAT.